Non Puerperal Uterine Inversion Due to Submucous Myoma: A Case Report - Salmeh Dadgar; Seyedeh Azam Pourhosseini (Tehran University of Medical Sciences, 2019)
Spontaneous uterine inversion rarely occurs in times other than the postpartum period. This condition is usually associated with the presence of a polypoid mass in the fundus, which is often a uterine leiomyoma or, in rare cases, a uterine sarcoma. Herein we report a case of a multipara, 51-year-old woman, presented with pelvic pain and vaginal bleeding. On the speculum examination, a circular mass of about 10 Cm, was observed in the vagina. In an ultrasound, a 55×62 mm intramural fibroid was observed. the patient was scheduled for surgery. After accessing the abdominal cavity, the patient was diagnosed with the uterine inversion. A longitudinal incision was made on the retraction ring. The base of the prolapsed mass was clamped at the incision site, and the mass was driven up into the vaginal canal and a total hysterectomy was performed.